Development of the teacher's professional subjectivity in the process of advanced professional training - Pilyugina, Svetlana A.; Sergeeva, Marina G. (Известия Саратовского университета: Новая серия. Серия Философия. Психология. Педагогика)
Introduction. Modern school education is undergoing renovation, thanks to the implementation of the national project “Education”. The contradiction between the need for a teacher to possess a number of professional competencies and their insufficient formation determines the request to institutions for additional professional education to form the teacher’s professional subjectivity which can create conditions for eliminating professional difficulties. The purpose of our research is to study the leading pedagogical condition for the development of professional subjectivity of the teacher. The main methods were literature analysis and pedagogical experiment. Theoretical analysis. The theoretical analysis has shown that there are different scientific views on professional subjectivity: as a specific ability of a person to design, implement, and evaluate their own activities; as a tool for adapting a person to a profession through education and self-education; as a system of skills for professional self-development and self-regulation of a person. Empirical analysis. Within the framework of empirical analysis and pedagogical experiment, we have identified different levels of development of professional subjectivity of the teacher. The use of creative tasks allowed us to conclude that it is an important pedagogical condition for the development of the teacher’s professional subjectivity. Conclusion. The development of the professional subjectivity of the teacher in an institution of a system of additional professional education is effectively carried out when the method of applying the system of creative tasks in teaching is used.